Comparative Efficacy of Wound Drainage and Non-Drainage in Posterior Spinal Surgery - Shakya, Bikram; KC, Bidur (Eastern Green Neurosurgery, 2024)
Background: The recent trend has been toward recommendation of nondrainage in spinal surgery. However, the use of drains following posterior spinal surgery is still controversial. It has been claimed that wound drainage confers no significant advantages, increases the risk of infection and the need for blood transfusion with the attendant risks of this therapy. Suction drainage is used to minimize infection, prevention of wound swelling, improvement of the local wound environment, prevent hematoma and /or seroma formation. The aim of this study was to determine the incidence of post-operative complications after posterior lumbar instrumentation with and without a subfascial drain. Methods: This is prospective analysis of 32 adult (≥18 years old) spine patients that underwent elective and emergency posterior lumbar instrumentation at Kathmandu Medical College Teaching Hospital, from January to December 2023. There were randomly assigned 16 (50%) patients who had a post-operative drain and 16 (50%) patients who did not have a postoperative drain (No-Drain: n=16; Drain-Use: n=16). Patient demographics, comorbidities, intra- and post-operative complication rates were collected for each patient. The primary outcome investigated in this study was pain, the need for post-operative transfusion, dressing changes, surgery – discharge interval, the rate of post-operative complications, specifically surgical site infections (SSI) and hematoma formation. Data was analyzed using SPSS statistics version 29 (IBM Corp., New York). Results: Our study revealed that no significant differences regarding wound infection (P = 1), hematoma, neurological injury, estimated blood loss (P = 0.3), or dry and moderate dressing drainage between the groups. There were no 30-day hospital readmission or incidence of 30-day wound dehiscence, draining wound or bleeding between both patient groups. Conclusions: There is no obvious advantage of the application of suction drains for spinal surgery. There was no significant difference in the rate of infection or wound healing and no patient developed a postoperative neurologic deficit. However, a decision of wound drainage or wound non-drainage should be individualized for each patient because many factors affect the outcomes.